The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1177/40.10.1527378
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical demonstration of dopamine-beta-hydroxylase and cytochrome B561 on the axonal reticulum in bovine sympathetic neurons.

Abstract: In sympathetic neurons the axonal reticulum can be considered an extension of the secretory pole of the Golgi apparatus. If this tubular system indeed represents the neurosecretory apparatus, it would likely contain on its membranes the enzymes involved in catecholamine synthesis. To test this hypothesis, we investigated the distribution of dopamine-beta-hydroxylase and cytochrome b561 in bovine splenic nerve and nerve terminals in the vas deferens with an immunogold procedure after glycolmethacrylate embeddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Also, at the light microscopical level the distribution of CGA-and cytochrome b,,,-IR in vas deferens is basically different from p38-IR. In addition, previous immunoelectron microscopic data clearly showed no colocalization of DPH and p38 on LDV in the bovine vas deferens (Quatacker et al, 1992). This is in agreement with the generally accepted idea that LDV and SSV form two distinct secretory pathways [see also reviews of De Camilli and Jahn (1990) and Matteoli et al ( 1991)…”
Section: Enrichment Of Sdvsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, at the light microscopical level the distribution of CGA-and cytochrome b,,,-IR in vas deferens is basically different from p38-IR. In addition, previous immunoelectron microscopic data clearly showed no colocalization of DPH and p38 on LDV in the bovine vas deferens (Quatacker et al, 1992). This is in agreement with the generally accepted idea that LDV and SSV form two distinct secretory pathways [see also reviews of De Camilli and Jahn (1990) and Matteoli et al ( 1991)…”
Section: Enrichment Of Sdvsupporting
confidence: 86%
“…Concerning the first finding, it has been demonstrated that two proteins present in LDV, i.e., DPH and cytochrome b561, are also present in the AR as visualized by a novel counterstaining technique (Quatacker et al, 1990(Quatacker et al, , 1992, confirming that the AR forms another amine-storing compartment (Tranzer, 1972). This membrane compartment extends from the trans-Golgi zone to the nerve terminal.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, with regard to our further discussion, it should be emphasized that these results do not exclude that part of the NPY might still be present in another subcellular structure, such as, for example, the axonal reticulum. This subcellular organelle has already been demonstrated, by immunocytochemical methods, to contain NPY, DbH, and cytochrome b 561 (Quatacker et al, 1992(Quatacker et al, , 1993 and may have, as appears from gradient centrifugation studies on splenic nerve axons, an equilibrium density similar to that of axonal LDCV (De Potter, 1976).…”
Section: Analytical Subcellular Fractionation Studies Of a Dog Spleenmentioning
confidence: 87%
“…Immunogold-silver particles also were associated with tubular membranes (Fig. 5B) that may represent the axonal reticulum, a membranous structure often found to be positive for LDCV markers (Quatacker et al, 1992;Annaert et al, 1994). Despite the high abundance of SSVs within synaptic profiles, immunogold-silver particles rarely were found to be affiliated with SSVs (Fig.…”
Section: The Cellular and Subcellular Localizations Of P64h1 In The Rmentioning
confidence: 88%